2002
DOI: 10.3102/01623737024003219
|View full text |Cite
|
Sign up to set email alerts
|

Below the Bar: Profiles of Students who Fail State Reading Assessments

Abstract: State and school districts are looking for policies they believe will improve student performance. As a result, assessments have proliferated, stakes have increased, and specific curriculum and instructional approaches are being mandated. In this study, we probed beneath students' failing scores on a state reading assessment to investigate the needs of struggling students and implications for policy. We found that scores on state tests mask distinctive and multifaceted patterns of students' reading abilities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 44 publications
12
133
1
Order By: Relevance
“…This approach aims to improve upon most randomized controlled trials of READ 180, which measure impact estimates on a single measure of reading comprehension and do not permit a direct test of the theory of instruction underlying the intervention (Lang et al, 2009;Slavin et al, 2008). READ 180 Enterprise targets multiple components of reading because the theory of instruction is that reading comprehension is the product of word reading and language comprehension (Gough & Tunmer, 1986) and that struggling readers have varying reading profiles (Buly & Valencia, 2002;Morris et al, 1998 i.e., the treatment-on-the-treated estimate (Angrist, Imbens, & Rubin, 1996).…”
Section: Study Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach aims to improve upon most randomized controlled trials of READ 180, which measure impact estimates on a single measure of reading comprehension and do not permit a direct test of the theory of instruction underlying the intervention (Lang et al, 2009;Slavin et al, 2008). READ 180 Enterprise targets multiple components of reading because the theory of instruction is that reading comprehension is the product of word reading and language comprehension (Gough & Tunmer, 1986) and that struggling readers have varying reading profiles (Buly & Valencia, 2002;Morris et al, 1998 i.e., the treatment-on-the-treated estimate (Angrist, Imbens, & Rubin, 1996).…”
Section: Study Goalsmentioning
confidence: 99%
“…Independent and modeled reading practice with leveled text (20 minutes) aims to increase reading motivation and subsequent time spent reading through self-selected high-interest books and audio books (Guthrie, 2003). Teacher-directed reading lessons tailored to the reading level of small groups (20 minutes) allows teachers to differentiate instruction (Tomlinson, 2001), a critical feature given the heterogeneity of student reading profiles (Buly & Valencia, 2002;Morris et al, 1998).…”
Section: Read 180: Program Theory and The Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, In most undergraduate English as a foreign language majoring departments, most significantly, the ultimate aim of English as a foreign language education is to acculturate students with English language major skills and to improve reading speed and comprehension of students in English (Buly & Valencia, 2002). Additionally, Beeson (2001) indicated that to complete successfully an academic programme of study to become English teachers, students must be able to read, comprehend, and apply materials from textbooks and journals.…”
Section: Introductionmentioning
confidence: 99%
“…They had an over-simplified view of what they really needed to learn and to activate in their brains, in order to read and write. From their findings, Buly and Valencia (2002) concluded that policies which mandate the use of phonics instruction for low-progress readers miss the needs of the majority of these learners.…”
Section: Strategies For Comprehending Textmentioning
confidence: 99%